Deteksi Menuju Aksi: Penguatan Literasi Informasi Kesehatan tentang Artritis Gout melalui Skrining dan Konseling Terintegrasi - Santy Irene Putri; Aris Widiyanto; Isnaini Qoriatul Fadhilah; Rizki Aqsyari D; Arie Jefry Ka'arayeno (Jurnal Medika: Medika, 2026)
Hyperuricemia is a condition of increased uric acid levels in the blood which plays an important role as an etiological factor in the occurrence of gout. Currently, gout is a public health problem that is increasing due to changes in lifestyle, consumption patterns, and low public knowledge about risk factors and their prevention. Misconceptions, such as the assumption that all joint pain is caused by gout and restricting the consumption of certain vegetables without scientific basis, are still widely found in society. This community service activity aims to increase public knowledge and awareness about gout through uric acid levels checks and the provision of health counseling. The activity was held in Mojorejo, Sragen, Central Java. The method used includes checking uric acid levels using a simple test tool followed by individual and group counseling. Counseling materials include the definition of gout, etiology, clinical manifestations, disease impact, prevention efforts, gout management, and traditional medicine. Evaluation was carried out through observation of active community participation and questions and answers during the counseling process. The results of the activity show high public enthusiasm, increased understanding of gout, and increased awareness to conduct routine health check-ups at health care facilities. This activity is expected to contribute to the promotive and preventive efforts of gout at the community level.